Balance sheets of financial intermediaries: Do they forecast economic activity? - Rodrigo M. Sekkel (Bank of Canada, 2014)
This paper conducts a real-time, out-of-sample analysis of the forecasting power of various aggregate financial intermediaries' balance sheets to a wide range of economic activity measures in the United States. I find evidence that the balance sheets of leveraged financial institutions do have out-of-sample predictive power for future economic activity, and this predictability arises mainly through the housing sector. Nevertheless, I show that these variables have very little predictive power during periods of economic expansions and that predictability arises mainly during the financial crisis period.
Keywords: C53; 330; Econometric and statistical methods